Retos y Oportunidades de la Auditoría de Sistemas Basada en Inteligencia Artificial y Aprendizaje Automático (2023)
This article discusses the challenges and opportunities of implementing artificial intelligence and machine learning in the field of systems auditing. Technological advancements have transformed the way businesses operate, and AI and ML can enable automating tasks, analyzing large volumes of data, reducing errors, increasing operational efficiency, and reducing costs.